The impact of hepatitis C burden: an evidence‐based approach. Issue 5 (26th January 2014) - Younossi, Z. M.; Kanwal, F.; Saab, S.; Brown, K. A.; El‐Serag, H. B.; Kim, W. R.; Ahmed, A.; Kugelmas, M.; Gordon, S. C.
Summary Background Infection with the hepatitis C virus (HCV) has been considered a major cause of mortality, morbidity and resource utilisation in the US. In addition, HCV is the main cause of hepatocellular cancer (HCC) in the US. Recent developments in the diagnosis and treatment of HCV, including new recommendations pertaining to screening for HCV by the Centers for Disease Control and Prevention and newer treatment regimens with high efficacy, short duration and the potential for interferon‐free therapies, have energised the health care practitioners regarding HCV management. Aim To assess the full impact of HCV burden on clinical, economic and patient‐reported outcomes. Methods An expert panel was convened to assess the full impact of HCV burden on a number of important outcomes using an evidence‐based approach predicated on Grading of Recommendations Assessment, Development and Evaluation methodology. The literature was summarised, graded using an evidence‐based approach and presented during the workshop. Workshop presentations were intended to review recent, relevant evidence‐based literature and provide graded summary statements pertaining to HCV burden on topics including the relationships between HCV and the development of important outcomes. Results The associations of HCV with cirrhosis, HCC, liver‐related mortality, type 2 diabetes mellitus, rheumatological diseases and quality of life impairments are supported by strong evidence. Also, there is strong evidence that sustained viral eradication of HCV can improve important outcomes such as mortality and quality of life. Conclusions The current evidence suggests that HCV has been associated with tremendous clinical, economic and quality of life burden.